OCCURRENCE OF PARREYSIA (PARREYSIA) WYNEGUNGAENSIS (LEA) (EULAMELLIBRANCHIATA) AND OPEAS ANNANDALEI GODWIN AUSTEN (STYLOMMATOPHORA) IN PORTO NOVO. - Natarajan, P; Soundararajan, R (Indian Journal of Fisheries, 2011)
The occurrence of the Lamellibranoh, Parreysia (Parreysia) wynegungaensis (Lea), and the gastrepod, Opeas aimandalei Godwin Austen in Porto Novo area has been reported. The former has been collected from muddy area of Vellar- Coleroon estuarine complex and latter from’ a crevice in a brackishwater well at Porto Novo.